Comparative phylogeography, a tool to increase assessment efficiency of polar assemblage resilience and vulnerability - Sands, Chester J.; Goodall-Copestake, William P.; Stöhr, Sabine; Narayanaswamy, Bhavani E.; Convey, Peter (Frontiers in Ecology and Evolution, 2024)
The Southern Ocean benthos is remarkably rich and diverse, and managed under a complexity of treaties and conventions, further complicated by geopolitical boundaries. Traditionally, conservation management is largely informed by species lists augmented, when data are available, by known vulnerability of the taxa. Species presence absence database resources are valuable tools with proven and positive management outcomes, however, in a vast, difficult to access and thus understudied region such as the Southern Ocean, there are large gaps in knowledge regarding the ecology, ecophysiology, life history and even species identity. Conservation biogeography identifies regions of conservation concern, rather than a species-by-species approach, but also relies on the availability of high-quality presence data from species lists and thus both approaches are undermined when species lists are inaccurate or species in general are poorly described. In addition, the data provide a snapshot of the current species diversity and have inadequate power to identify the processes underlying the patterns uncovered. Identifying historical processes common to shaping diversity (species or genetic) can be generalized across assemblages and regions, providing a more robust basis for conservation policy and decisions. In this study, largely based on consideration of Southern Ocean ophiuroids, we discuss the challenges inherent in using species lists, the power and limitations of genetic analyses, and revisit previous suggestions of building a spatial model of diversity that includes underlying evolutionary relationships transcending the simple species diversity approach, and that is applicable to assemblages, rather than just to individual taxa.